Civil Society Pasca Negara Birokratik Otoritarian Orde Baru - Rofieq, Ainur (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2012)
Democratization process in Indonesia cannot be separated from the role of civil society which develops through nongovernmental organization. After the collapse of New Order bureaucracy regime, the process seems like apparent death. The confusion over the emergence of ‘the anti-democracy wave’ is increasingly filed through. Therefore, the hope for the raise of civil society as driving force for democratization process emerges, so that the inversion to the new authoritarianism cannot be happened.